Ant Financial : flourishing farmer loans at MYbank - Xu, Jingyue; Rosenthal, Jean; Sudhir, K.; Song, Hua; Zhang, Xia; Song, Yuanfang; Liu, Xiaoxi; Elias, Jaan (London : Yale School of Management, 2017)
In 2015, Ant Financial's MYbank (an offshoot of Jack Ma's Alibaba company) was looking to extend services to rural areas in China through its Flourishing Farmer Loan program. MYbank relied on the internet to communicate with loan applicants and judge their credit worthiness. Initial tests of the program had proved promising, but could MYbank operate the program at scale? Would its big data and technical analysis provide an accurate measure of credit risk for loans to small customers? Could MYbank rely on its new credit-scoring system to reduce operating costs to make the program sustainable?
Originally published in Xu, J., Rosenthal, J., Sudhir, K., Song, H., Zhang, X., Song, Y., Liu, X., & Elias, J. (2017). Ant Financial: Flourishing farmer loans at MYbank. Global Network Case 102-16. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://cases.advancedmanagement.net/ant-financial.
Description based on XML content.
Keywords: elektronické knihy; electronic books; ArabNet Technology (Firm); Farm management -- China; Farms -- Economic aspects -- China; Agricultural credit -- China